Chemical and physical pretreatments of microalgal biomass - Rodrigues, Brígida (2020)
Non-axenic microalga Chlorella sorokiniana was cultivated in batch cultures, and its total sugar composition was determined. The microalga under study showed a total sugar concentration of 21.44 ± 0.46% (w/w). The effects of freeze-drying, oven-drying, freezing and thawing, chemical and the combination of hydrothermal and chemical pretreatments were evaluated. In the combined pretreatment different concentrations of H2SO4 and reaction times were also optimized. It was possible to determine that the sugar extraction yields more significant were 59.5% for the lyophilization, 6.2% with 6 cycles of freeze and thawing and around 100% for 2 and 4% (v/v) of H2SO4 at 121 °C for 30 min. Some of the methods that were described in this study are interesting to facilitate cost-efficient conversion of microalgal biomass into biofuels.